Laboratórios do Departamento de Materiais Odontológicos e Prótese - Bacaneli, Ana Marcelina dos Santos; Gonçalves, Carlos Alberto; Cobo, Eduardo Rodrigues; Inácio, Jander de Carvalho; Gon, Rosemeire de Oliveira Machado (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação Carlos Alberto Gonçalves Eduardo Rodrigues Cobo Jander de Carvalho Inácio